Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12891-021-04015-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of relief and residual low back pain after discectomy in patients with lumbar disc herniation: analysis using a detailed visual analog scale

Abstract: Background Several authors have reported favorable results in low back pain (LBP) for patients with lumbar disc herniation (LDH) treated with discectomy. However, detailed changes over time in the characteristics and location of LBP before and after discectomy for LDH remain unclear. To clarify these points, we conducted an observational study to determine the detailed characteristics and location of LBP before and after discectomy for LDH, using a detailed visual analog scale (VAS) bilaterally… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Full text of the remaining 52 articles was carefully evaluated. 9 studies that met the inclusion and exclusion criteria were eventually included in this meta-analysis [22][23][24][25][26][27][28][29][30]. A total of 2505 patients were included in this analysis, and the basic characteristics of the included study are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Full text of the remaining 52 articles was carefully evaluated. 9 studies that met the inclusion and exclusion criteria were eventually included in this meta-analysis [22][23][24][25][26][27][28][29][30]. A total of 2505 patients were included in this analysis, and the basic characteristics of the included study are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Prior research has produced conflicting findings on the subject. While it has been reported that patients with Modic grade I change to experience the same level of pain relief as those without Modic changes, several studies indicate that patients with Modic or Pfirrmann changes may experience more residual pain or have a greater risk of recurrent disc herniation [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…In LDH, the patient often complains LBP to some degree (8). It was reported that LBP in LDH may be caused by multiple factors such as discogenic LBP, radicular LBP that is relieved by nerve root decompression, and the LBP due to endplate degeneration (9). Most patients with lumbar disc herniation will have paresthesia, but this patient has no paresthesia on foot.…”
Section: Discussionmentioning
confidence: 99%